ANALISIS DINAMIKA PERMASALAHAN IMPLEMENTASI ANGGARAN PEMERINTAH DAERAH DI INDONESIA - Rahmat Salam (AKSELERASI: Jurnal Ilmiah Nasional, 2020)
The budgeting process is central to every administration be it the central government, local governments and the private sector because financial control is perhaps the most effective coordination tool. The scope and nature of government operations as a whole are determined by the allocations for the various programs. In fact, human nature has never been proven compared to when humans struggle to get a larger than usual share of the funds. This paper examines budgeting at the local government level, its preparation, problems and prospects. The study found that there was a wide gap between the budget plan and its implementation which resulted in the failure to fulfill political promises and the increasingly high expectations of society. The widespread dissatisfaction of the masses with the local government contributed greatly to the slow pace of local community development. This paper makes several recommendations that will reduce the incidence of budget deficits in the Government.